The Effect of Endorphin Massage on the Intensity of Pain in the Normal Primipara Mother in BPS Ririn Dwi Agustin Jombang - Hidayatun Nufus (Health Notions, 2018)
Background: Maternal primipara at Connecticut's average of 17 per month primipara mothers feel very great pain in stage I. The mother felt a severe pain and anxiety. Purpose: To know the influence of endorphin massage to stage I pain intensity of normal childbirth mother primipara at BPS Ririn Dwi Agustin Jombang. Methods: This research utilized quasi experimental design, the design used was posttest only control group design. Respondents were all childbirth mothers (primipara) at Juny-August 2018, selected by concecutive sampling technique. Results: Childbirth pain at most control group experience severe pain as many as 10 people (66.7%). Respondents who experience medium pain as many as 4 people (26.7%), and very severe pain as many as 1 person (6.7%). Childbirth pain at most treated group experience mild pain as many as 9 people (60.0%). Respondent who experience medium pain as many as 4 people (26.7%), and severe pain as many as 2 people (13.3%). The p-value of hypothesis testing was 0.000. Conclusion: There is influence of endorphin massage to stage I pain intensity of normal childbirth mother primipara (p value = 0,000 < 0,05). Keywords: endorphin massage; stage I pregnancy; pain intensity